ACTIVE SOCIAL PROGRAMS AND THEIR STRATEGIC ADVANTAGES IN LABOR MARKET DEVELOPMENT - Stoyanov, Evgeniy (Journal of Economic Development, Environment and People, 2016)
The active programs and measures on the labor market are the subject of increasing interest and comment not only because expectations for tangible effects, but also because of the relatively significant financial resources necessary for their implementation. The paper discussed the active social programs and their strategic advantages in labor market development considering the methodology of their development and accenting the role of human resources and innovative technologies.